Development of an experimental tilt-wing VTOL unmanned aerial vehicle - Venter, Jacob (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2006.